Concept and Reality of Natural Law - Interdonato, Francisco (1987)
The text analyzes the concept of natural law, which is based on universal principles that guide human conduct towards the “good”, independently of the provisions of positive law. The author points out that natural law is not a human creation, but a reality discovered in the very essence of the human being, which manifests itself through practical judgments that allow discerning between what is right to be done and what should be avoided. He argues that law transcends epochs and cultures, being inherent to human nature, which is reflected in norms that prohibit murder, theft or deceit. To that extent, it is emphasized that these “duties” are a requirement that emanates from the personal being. Likewise, unlike positive laws, natural law responds to immutable principles and does not depend on human codifications, but on the rationality of human beings. However, its application may vary according to historical or cultural circumstances, as occurred with slavery. In this regard, the author argues that the historical existence of slavery does not contradict the fundamental principles of this law, since this practice can be classified as a fourth-class precept within the hierarchy of natural law. In essence, this law connects the intrinsic morality of man with universal values, establishing an ethical order superior to human laws.